2020
DOI: 10.1039/c9cp06284j
|View full text |Cite|
|
Sign up to set email alerts
|

The corrosion inhibition of stainless steel by ferrocene–polyoxometalate hybrid molecular materials – experimental and first principles studies

Abstract: The corrosion inhibition mechanism for SS316 coated with FcPMo hybrid material is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…17,18 Such excellent properties also make them attractive as oxidizing and film-forming corrosion inhibitors. 19 Lomakina et al used several heteropolytungstates as corrosion inhibitors of aluminum and alloys in high-temperature water. 20 Liang et al found that Na 3 PW 12 O 40 and H 4 PW 11 VO 40 could effectively retard the corrosion of carbon steel in 55% LiBr solution.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Such excellent properties also make them attractive as oxidizing and film-forming corrosion inhibitors. 19 Lomakina et al used several heteropolytungstates as corrosion inhibitors of aluminum and alloys in high-temperature water. 20 Liang et al found that Na 3 PW 12 O 40 and H 4 PW 11 VO 40 could effectively retard the corrosion of carbon steel in 55% LiBr solution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…POMs, as a kind of well-defined and nano-sized anionic metal-oxygen cluster possessing low toxicity, high electron affinity, and structural stability, have been widely applied in energy-related fields. , Such excellent properties also make them attractive as oxidizing and film-forming corrosion inhibitors . In 1994, Lomakina et al .…”
Section: Introductionmentioning
confidence: 99%
“…WL measurement was performed by weighting the coupons aer regular immersion time and the SS weight loss was considered as the mean weight loss of triplicate specimens under the same conditions. The degree of metal surface coverage (q), and the inhibition efficiency, IE (%), of the investigated compounds were calculated respectively using eqn (1) and (2).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, researchers have being addressing this subject in many ways, especially to present fundamental aspects of metal corrosion phenomena and corrosion inhibition across scientic research. [1][2][3][4] Most research projects deal with the electrochemical principles and chemical aspects of corrosion inhibition, such as the stability of metals and their alloys, different corrosive media, quantum chemical aspects, and also with the various surface analysis techniques that are used in industry and the academic eld to deepen the diagnosis and studies for corrosion inhibition. 5 In the same context, the understanding of stainless steel corrosion is also considered an essential topic for academic and industrial elds 6 due to its wide applications in acidic industries such as petroleum platforms, oil well acidication, chemical handling, and water treatment, as well as in surface treatment plants for descaling, pickling, and rust removal.…”
Section: Introductionmentioning
confidence: 99%
“…[8] To address this issue, several works have been recently focused on the use of polyoxometalates (POMs) as an eco-friendly alternative of oxoanions as corrosion inhibitors. [9][10][11][12] POMs are metal-oxo cluster anions based on early transition metals (e. g. Mo, W, V) in a high oxidation state. These complexes are formed in acid medium by self-assembly of polyhedral oxometallic units whose centres are occupied by a metallic atom (M) and the vertices by oxygen atoms.…”
Section: Introductionmentioning
confidence: 99%